Sensory Entrainment Mechanisms in Auditory Perception: Neural Synchronization Cortico-Striatal Activation - Sameiro-Barbosa, Catia M.; Geiser, Eveline (Frontiers in Neuroscience, 2016)
The auditory system displays modulations in sensitivity that can align with the temporal structure of the acoustic environment. This sensory entrainment can facilitate sensory perception and is particularly relevant for audition. Systems neuroscience is slowly uncovering the neural mechanisms underlying the behaviorally observed sensory entrainment effects in the human sensory system. The present article summarizes the prominent behavioral effects of sensory entrainment and reviews our current understanding of the neural basis of sensory entrainment, such as synchronized neural oscillations and, potentially, neural activation in the cortico-striatal system.